TEACHING VOCABULARY THROUGH CHANTS AND STORYTELLING STRATEGIES TO THE FIFTH GRADE PUPILS OF SDN 2 PALEMBANG - Nian Masna Evawati; Darmaliana - - (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2014)
The fifth grade pupils at elementary school in Palembang had difficulties in learning vocabulary and pronunciation. These vocabulary and pronunciation learning problems made the writer interested in teaching vocabulary and pronunciation through chants and storytelling strategies to overcome pupils’ difficulty in learning vocabulary and pronunciation. The objectives of the study were to find out whether or not (a) there was a significant difference in vocabulary achievement and pronunciation ability of the pupils before and after they were taught through chants strategy?, (b) there was a significant difference in vocabulary achievement and pronunciation ability of the pupils before and after they were taught through storytelling strategy?, and (c) there was a significant difference in vocabulary achievement and pronunciation ability of the pupils who were taught through chants strategy as compared to those who were taught through storytelling strategy. The population was all the fifth grade pupils of SDN 2 Palembang. The samples were 60 pupils. This study was experimental. The data were analyzed by using t-tests (paired samples t-test and independent samples t-test). The findings showed that chants strategy could increase pupils’ vocabulary achievement (t=10.285, α<0.05) and improve their pronunciation ability (t=9.607, α<0.05) significantly. Storytelling strategy could also increase pupils’ vocabulary achievement (t=12.751, α<0.05) and improve their pronunciation ability (t=5.705, α<0.05) significantly. In addition, there was no significant difference in vocabulary achievement (t=1.725, α>0.05) and pronunciation ability (t=1.680, α>0.05) between the pupils who were taught through chants strategy and those who were taught through storytelling strategy.